1998
DOI: 10.1093/carcin/19.4.611
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and induction of apoptosis in human cancer cell lines by tea polyphenols

Abstract: In order to study the biological activities of tea preparations and purified tea polyphenols, their growth inhibitory effects were investigated using four human cancer cell lines. Growth inhibition was measured by [3H]thymidine incorporation after 48 h of treatment. The green tea catechins (-)-epigallocatechin-3-gallate (EGCG) and (-)-epigallocatechin (EGC) displayed strong growth inhibitory effects against lung tumor cell lines H661 and H1299, with estimated IC50 values of 22 microM, but were less effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
335
6
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(367 citation statements)
references
References 21 publications
22
335
6
4
Order By: Relevance
“…41,42 It is hypothesized that tea consumption may lower CRC risk through its antioxidant components protecting colonic epithelial cells against oxidative radicals. 43,44 Despite the consistently observed protective effect of tea components in animal studies, a protective effect has, in general, not been demonstrated in epidemiological studies, 11,13 and is further confirmed by the present study. However, disparities can be observed between findings from Western and Asian studies, which might be caused by differences in type of tea (black or green) consumed.…”
Section: Discussionsupporting
confidence: 79%
“…41,42 It is hypothesized that tea consumption may lower CRC risk through its antioxidant components protecting colonic epithelial cells against oxidative radicals. 43,44 Despite the consistently observed protective effect of tea components in animal studies, a protective effect has, in general, not been demonstrated in epidemiological studies, 11,13 and is further confirmed by the present study. However, disparities can be observed between findings from Western and Asian studies, which might be caused by differences in type of tea (black or green) consumed.…”
Section: Discussionsupporting
confidence: 79%
“…For example, we have demonstrated that, depending on the cell lines and culture conditions, EGCG-induced apoptosis can be completely or partially blocked by the addition of catalase in the culture medium, suggesting that the apoptosis is mediated by H 2 O 2 [21,22]. We also found that catalase partially blocked EGCG-induced apoptosis and also abolished the effects on TGFβ signaling in transformed human bronchial epithelial cells (21BES) [23].…”
Section: Discussionmentioning
confidence: 94%
“…A difference in the response of the two probes to changes in cellular glutathione status has been reported previously 24 and further suggests that DHR and DCFH possess differing ranges of reactivity. There is an increasing trend to use DCFH or DHR oxidation as evidence of H 2 O 2 production 7,37 and although the probes do react with peroxide, they are sensitive to a variety of other free radical species. 39 The fact that there is an increase in DCFH oxidation in UVA-irradiated, EGCGtreated cells suggests that DCFH may react with reactive species generated as a result of the oxidation of EGCG through scavenging UVA ROS or with an EGCG radical itself.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Several mechanisms have been proposed by which these compounds exert their anti-tumorigenic action: these include the blockade of growth factors binding to their receptors, 10 phosphorylation (activation) of mitogen-activated protein kinases (MAPKs) 11,12 possibly resulting in the observed induction of Phase II drug-metabolizing enzymes, 13,14 and the generation of oxidative stress leading to apoptosis. 7,9 In the face of an oxidative challenge, however, it is now well documented that green tea catechins act as antioxidants. For example, EGCG abrogates oxidation by hydrogen peroxide both in a cell free system 15 and in terms of DNA single-strand break damage.…”
mentioning
confidence: 99%